Validação de uma matriz avaliativa do processo de enfermagem no contexto hospitalar - Amaral, Jocelio Matos (2023)
The Nursing Process (NP) is an important organizing method of care, through clinical, legal ethical, and scientific reasoning, as well as documentation of professional practice. However, the implementation and execution of the NS often occur in a fragmented way and are dissociated from the local realities. Through state-of-the-art review and technical visits to hospitals that are national references on the NP, the incipient initiatives of the NS evaluation in the hospital context were identified. Therefore, the present thesis aimed to validate the content of an evaluative matrix for the nursing process in the hospital context. To that end, a methodological study with a cross-sectional design was developed, which was submitted to a validation process, using the Content Validity (CV) technique. Thus, the construction and validation of the evaluation matrix were based on four methodological steps, according to the theoretical and methodological framework adopted, described as follows. First step: bibliographical research and selection of key references. Second step: construction of the logic model and the analysis and judgment matrix (AJM) from the Situational Strategic Planning (SSP) moments and other select references. Third step: content validation by an expert committee. To do so, the Delphi technique was used through Global and Item Evaluation. Two rounds were carried out with 11 judges joining. Fourth step: analysis of the content validation data by calculating the Concordance Rate (CR) and the Content Validity Index (CVI). At the end of the two rounds, the matrix had an agreement rate of 90% for the form and 100% for the other general aspects of the matrix. It also had an agreement rate of 100% for comprehension and representativeness of the matrix domains. For the CVI, the items had a total of 0,97 for clarity and 0,98 for representativeness. Therefore, the content of the matrix was considered validated by the judges and able to evaluate the NP, which can thus contribute to support institutional initiatives for consolidation of the NP in nursing services.